A feasibility integrated approach in the promotion of solar house design - Atikol, U.; Abbasoglu, S.; Nowzari, Raheleh (Wiley, 2013)
In many countries, although solar energy is plentiful, due to technical and economic issues, micro-scale solar energy technologies have not properly found their places in the market. The present work demonstrates the convenience of employing economic feasibility assessments together with engineering analyses before applying solar strategies during the design stages, in order to convince house owners that these solar technologies can be economically viable. In a case study, this approach is tested for a real house project developed in North Cyprus (NC) in which solar energy applications for electricity generation, hot water preparation, space heating and passive cooling are investigated. It is reported that grid-connected photovoltaic (PV) systems would be economically feasible with savings-to-investment ratio (SIR) values of 2.9 to 3.4. A thermal performance analysis is carried out for a thermal storage wall (TSW) together with a direct solar gain (DSG) window in the living room. It is discovered that the temperature range of the living room was within 1822 degrees C throughout the majority of winter days. This application is also proved to be economically feasible with an SIR of 1.3, compared to installing an 18,000Btu/h heat pump. It is determined that both locally produced solar water heaters and imported solar water heaters (ISWHs) are economically viable compared to using a 3-kW storage-type electric water heater. Their SIR values are estimated to be 7.5 and 3.7, respectively. A solar-assisted stack-effect ventilation (SEV) system is verified to have techno-economic feasibility and is also useful in concealing the unattractive cold and hot water storage tanks on the roof. The prospective house owner decides to invest 3840 EUR in installing a grid-connected PV system of 1 kWp, an ISWH, a DSG window, building a TSW for space heating and a SEV system with an overall SIR value of 3.2. This procedure can be developed into a government policy where all these assessments are made mandatory to increase the awareness of the home builders before they make their decisions about the final designs of their houses. The present work demonstrates the convenience of employing economic feasibility assessments together with engineering analyses before applying solar strategies during the design stages, in order to convince house owners that these solar technologies can be economically viable. In a case study, this approach is tested for a real house project developed in NC in which solar energy applications for electricity generation, hot water preparation, space heating and passive cooling are investigated. Copyright (c) 2013 John Wiley & Sons, Ltd.
Keywords: North Cyprus; photovoltaic; solar house; solar water heating; stack-effect ventilation; Trombe wall